An improved general class of estimators for finite population mean in simple random sampling. Issue 11 (3rd June 2022) - Shabbir, Javid; Gupta, Sat; Masood, Saadia
Abstract: Recently Pal et al. introduced a mean estimator which generalized most of the known mean estimators. We introduce a class of estimators that performs better than Pal et al. estimator. Expressions for bias and MSE for the proposed estimator are derived up to first order of approximation. We use the six datasets for numerical comparison.